THE INFLUENCE OF THE HUMAN FACTOR ON THE EMERGENCY AIR TRANSPORT (Transport systems and technologies, 2018)
The actuality of the human factor problem is related to the fact that personnel are the source of aviation incidents in modern aviation Statistics show that despite constant efforts to improve flight safety (BP), in recent years, there has been no significant decrease in accidents. Three out of four incidents occur because of a person’s functional unreliability: misunderstanding the situation, making erroneous decisions and, as a consequence, unsafe actions are the main ones The reasons for the majority of incidents Despite the fact that the level of safety of modern aviation is very high, the growth of air traffic and passenger capacity of the aircraft makes the price of each error unacceptably high, while the complexity and saturation of the modern air transport system (ATC) by automation make a person’s mistake extremely likely, If no effective means of preventing it are found, sotoday the main emphasis in the struggle for flight safety is aimed at a person.
Keywords: aviation, aviation accident, aviation transport system, flight safety, air transport, human factor